The golden city : A novel - Twelve Hawks, John (New York : Vintage Books, 2009)
Gabriel comes close to finding his father only to encounter an unimaginable new threat, while his brother Michael, firmly allied with the enemy, endeavors to wrest power from the leaders of the Brethren.
Keywords: Brothers -- Fiction; Paranormal fiction; Suspense fiction